Proposed Strategies for Improving Safety Management in Irrigation Projects Based on SWOT–AHP (Architecture Image Studies, 2025)
This research aims to improve safety management in irrigation projects and identify the most suitable strategies for project implementation that enhance their potential to promote safety and development. To achieve this, the SWOT-AHP methodology was used, which enabled us to identify six strategies: (1) Establishing a centralized digital system for documenting, analyzing, and reporting incidents; (2) Implementing comprehensive specialized training programs (HSE, ISO 45001, OSHA) for engineers and technicians in cooperation with recognized international organizations; (3) Upgrading outdated equipment and introducing modern maintenance techniques to enhance reliability and reduce operational risks; (4) Aligning Iraqi safety law with international standards and directly integrating safety requirements into contract documents; (5) Improving monitoring and follow-up mechanisms by activating the role of the occupational safety and health unit and using technology-supported inspection tools; (6) Strengthening cooperation with universities and research centers to develop advanced methodologies in safety engineering and specially designed training modules. CR = 0.093